Heck-Matsuda Reaction Catalyzed by Heterogeneous Palladium Catalysts - Oger, Nicolas; Le Grognec, Erwan; Felpin, Francois-Xavier (Current Organic Chemistry, 2015)
This review gives a complete picture of the Heck-Matsuda reaction of arenediazonium salts with olefins catalyzed by heterogeneous palladium catalysts. The nature, preparation and characterization of the different forms of heterogeneous palladium catalysts are presented, while their activity on the Heck-Matsuda reaction is critically discussed.
Keywords: Arenediazonium salt